HGG-24. COMPREHENSIVE GENOMIC ANALYSIS OF PEDIATRIC GLIOMAS UNCOVERS NOVEL MUTATIONS IN HISTONE-ENCODING GENES. (23rd April 2019) - Bonner, Erin; Kambhampati, Madhuri; Gaonkar, Krutika; Mueller, Sabine; Resnick, Adam; Raman, Pichai; Nazarian, Javad
Abstract: In order to define the mutational landscape across histone genes in pediatric CNS cancers, we surveyed 1, 000 patients from the Children's Brain Tumor Tissue Consortium (CBTTC) cohort, representing 1, 100 samples from 35 studies. In addition, we amassed genomic data from 152 pediatric high grade glioma subjects (114 WGS, 38 WES) representing both upfront biopsies and autopsy specimens. Using existing and newly generated genomic data, we comprehensively mapped the histone mutation landscape in pediatric gliomas. We identified previously unknown and novel histone mutations, mostly associated with midline gliomas (pontine and thalamic). Mutations were classified as protein damaging (causing a change in amino acid or frameshift), rare (present in less than 0.01% of the population), and somatic by comparison to matched germline DNA, or to a large panel of normal brain samples from the CBTTC cohort (n=40). Mutations were found in both linker and core histone genes, validated by Sanger sequencing, and defined in the context of their clinical impact. The majority of these mutations are expected to decrease protein stability, and to perturb post-translational modifications (in particular methylation and/or phosphorylation) at the protein level. Novel mutations were identified in tumor samples harboring K27M in H3.3 and H3.1, as well as in tumors classified as histone wild type (due to absence of K27M mutation). Subjects harboring novel histone mutations were found to have higher overall mutational load, and unsupervised clustering of methylation data has identified distinct epigenetic patterns within H3.3/3.1 K27M subjects with and without novel histone mutations. We also assessed co-occurrence of novel histone mutations with known partner mutations, and identified genes encoding DNA-binding proteins significantly associated with novel linker histone mutations. In vitro studies are underway to define the biological role of novel histone mutations in tumorigenicity.